Organisational Change in Public Service - Dian Ekowati (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2021)
This study aims to investigate institutional logics underlying the initiation of change management process in public sector organisations. Organisational Institutionalism is used to frame the analysis. The study took place in three different public organisations in the Province of East Java, including one-stop-service for licencing as well as that of vehicle registration, taxing and insurance and also from local health authority. Qualitative method was employed to analyse information gathered through semi-structured interviews with 35 respondents. The study unveiled various institutional logics underlying the adoption of changes and innovation in the organisations. It ranged from the most common reason of improving performance gaps up to the needs to clean the organisation’s name and build a better image. The study contributes to the idea that organisation’s previous experiences as well as perceived institutional character affect the needs to conduct changes. https://doi.org/10.21632/irjbs.14.2.159-170